1993
DOI: 10.1007/bf00004574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormone on gonadotropin-induced steroid production in medaka, Oryzias latipes, ovarian follicles

Abstract: Blood and ovarian samples were collected at intervals of 4h prior to spawning time from medaka (Oryzias latipes) that were maturationally synchronized with artificial photoperiod (14h light: 10h dark). Plasma estradiol-17β (E2) levels increased rapidly from 16h before spawning and peaked at 8h before spawning. Follicle-enclosed oocytes (ovarian follicles) at different stages of development were isolated from the ovaries and used to study the in vitro effects of thyroid hormone (triiodothyronine; T3) on pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Since reproductive roles for GH (reviewed in LeGac et al 1993), IGFs (Huang et al 1998, Weber & Sullivan 2005, thyroid hormones (Soyano et al 1993, Tambets et al 1997 and F (reviewed in Mommsen et al 1999) have all been demonstrated in fish, gonadal changes in their expression further indicate multiple pathways of oestrogen effect on sexual development. Given the lack of knowledge on the function of locally produced GH and IGF-I, and of the roles of THRs and GRs in the gonad, however, it is difficult to interpret these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Since reproductive roles for GH (reviewed in LeGac et al 1993), IGFs (Huang et al 1998, Weber & Sullivan 2005, thyroid hormones (Soyano et al 1993, Tambets et al 1997 and F (reviewed in Mommsen et al 1999) have all been demonstrated in fish, gonadal changes in their expression further indicate multiple pathways of oestrogen effect on sexual development. Given the lack of knowledge on the function of locally produced GH and IGF-I, and of the roles of THRs and GRs in the gonad, however, it is difficult to interpret these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, thyroid hormones are undoubtedly involved in synergizing with gonadotropin during oocyte maturation. The existence of a thyroid hormone receptor in the gonad has also been proved in several teleosts such as perch (Chakraborti et al 1986) and medaka (Soyano et al 1993). This permits the enhancement of thyroid hormone on gonadotropin action.…”
mentioning
confidence: 91%
“…This criterion can be challenging to meet with females of fish species that are asynchronous, fractional spawners, as inter-individual variation in ovarian weight can be high during the spawning cycle. Two approaches researchers have used to overcome this limitation are synchronization of spawning cycles through environmental manipulations (Soyano et al, 1993; Van den Belt et al, 2001), and more commonly, simply including sufficient numbers of replicates in an exposure tank to "average" out the variation across individuals.…”
mentioning
confidence: 99%
“…With regard to medaka and zebrafish, the limited data make it difficult to make comparisons with fathead minnows, other than evidence for cyclic levels of E2 in females. For example, in the medaka, E2 plasma concentrations appear to oscillate during the spawning cycle, with peak concentrations occurring approximately 8 hours before spawning (Soyano et al, 1993). No published data on E2, T, or 11-KT levels in zebrafish could be found.…”
mentioning
confidence: 99%
See 1 more Smart Citation